2015
DOI: 10.5007/1980-0037.2015v17n3p269
|View full text |Cite
|
Sign up to set email alerts
|

Superioridade numérica altera a demanda física de jogadores de Futebol durante Pequenos Jogos

Abstract: -Small-sided games are used for the training of soccer athletes because they replicate the physical and technical demands in a game-related context. Different game configurations are possible, such as differences in the number of players, i.e., 3vs.3 or 4vs.4. However, unbalanced situations are common during a competition, but have been little studied in small-sided games. This study compared the physical demands of 3vs.3, 4vs.3 (additional player in the attacking team) and 3vs.3+2 (two supporting players arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…To the best of our knowledge, no other study has considered a similar design to investigate the influence of variability in the number of players on the external training load. The work with the most similar results to our study was reported by Praça, Custódio, and Greco [41]. They concluded that the physical demands of players were reduced when adding an element to a team compared to situations in which they played in numerical equality.…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge, no other study has considered a similar design to investigate the influence of variability in the number of players on the external training load. The work with the most similar results to our study was reported by Praça, Custódio, and Greco [41]. They concluded that the physical demands of players were reduced when adding an element to a team compared to situations in which they played in numerical equality.…”
Section: Discussionsupporting
confidence: 89%
“…6.4 ± 1.7 5.1 ± 1.2 4.9 ± 1.6 3.5 ± 1.3 2.9 ± 1.1 −1.5 (−3.3 to 0.3) −0.3 (−1.8 to 1.3) −1.4 (−3.7 to 0.9) −2 (−3.5 to −0.5) Frontiers in Psychology | www.frontiersin.org player(s), increasing the distance covered at higher intensities as a result of an attempt of the team in inferiority to recover the ball and cover possible passing lines. It was also expected that individuals at this stage of players' development should be able to have a better tactical knowledge and understanding of the different affordances according to SSGs manipulations (Praça et al, 2015). Clearly, in High-Sup and Sup (4v2 and 4v3), players have more space and can spread around the playing area to easily keep ball possession; in Inf and High-Inf (4v5 and 4v6), players need to cover more distances at higher intensities to recover possession, due to a higher playing area density (playing area divided by the number of players).…”
Section: Discussionmentioning
confidence: 99%
“…Soccer is indicated to be a dynamic, unpredictable sport (Müller et al, 2016), requiring appropriate decisions due to the situational changes -which are constant during the game. The fundamental principles of soccer are: passing, shooting, ball control, heading, dribbling, feinting and tackling (Praça, Custódio, & Greco, 2015). According to Memmert (2010), passing is the main foundation to be successful in soccer.…”
Section: Discussionmentioning
confidence: 99%